Differences in Clinical Profiles and Outcomes of Children with Dengue during the 2019 and 2022 Outbreaks: Experience from a Tertiary Hospital, Chattogram, Bangladesh - Das, Aparup Kanti; Choudhury, Zabeen; Amin Chowdhury, Muhammad Jabed Bin; Alam, Md Shah; Datta, Mitra; Shil, Sunanda; Chowdhury, Pranab; Das, Suparna (Journal of Chittagong Medical College Teachers’ Association, 2023)
Background: It was observed that the clinical presentation of dengue fever has been changed with time since its first outbreak in 2000 in Bangladesh. In 2019, Bangladesh experienced the largest dengue outbreak in its history and the 2022 outbreak is the second-largest outbreak since 2000. The study aimed to describe the clinical presentations and outcomes of dengue infected children in 2022 in a tertiary hospital in Bangladesh along with its comparison to previous 2019 outbreak witnessed in this hospital. Materials and methods: This hospital-based descriptive study was conducted in the largest tertiary care hospital in Chattogram, Bangladesh. A total of 472 (192 in 2019 and 280 in 2022 outbreak) laboratory-confirmed dengue cases were analyzed. The demographic, clinical manifestations and outcomes of the cases of the 2022 outbreak was compared with previous (2019) outbreak by using SPSS windows version 23. Results: The median age of the children were 8 and 7 years, respectively in 2019 and 2022, with a significantly higher proportion of infant cases in 2022 (11.8% vs. 3.6%) than 2019.Male predominance and higher proportion of patients from urban area were observed in 2019, and the trend was more prominent in 2022 outbreak without any statistical significance. The 2022 outbreak is characterized by a higher proportion of vomiting (60.7% vs. 47.9%), body ache (37.1% vs. 14.5%), hemorrhagic manifestations (19.3% vs. 11.4%), respiratory distress (10.7% vs. 5.2%), and retroorbital pain (8.9% vs. 4.2%) than the 2019 outbreak. Abdominal pain (42.9% vs. 91.7%) and diarrhea (4.6% vs. 7.8%) and shock (9.4% vs 6.1%) were observed less frequently in 2022 outbreak than the 2019. Median length of hospital stay was significantly more during 2022 than the 2019 outbreak (5 days vs. 4 days). There was no case fatality in 2019 outbreak, but 5 (1.8%) patients expired in 2022. Conclusions: The 2022 outbreak was associated with unusual high number of cases in the last three months of the year. The median age of dengue children has decreased and younger patients were more susceptible. JCMCTA 2023 ; 34 (1) : 116-120